Active Sidestick for Steer-by-Wire Systems - Chakirov, Roustiam; Vagapov, Yuriy; Gaede, Andreas (Journal of Electrical and Electronics Engineering, 2010)
The introduction of new steering concepts Steer-by-Wire (SBW) gives possibility to replace the conventional steering wheel by an alternative user interface such as a sidestick. In SBW system the sidestick can be used as user input element instead of a steering wheel. The implementation of sidestick in the Human-Machine-Interface (HMI) allows combining the conventional steering consisting of a steering wheel, an accelerator and a brake pedal into a single element. Also the implementation of the sidestick creates new, interesting and flexible design options which can be used to transform the driver's spatial environment. This article describes an active sidestick for a vehicle which has been developed, integrated and tested in accordance of haptic, ergonomic and safety relevant requirements. The control strategies used for the active attenuators of the sidestick have been investigated and optimised using a Simulink model. [PUBLICATION ABSTRACT]